Struktur Pendapatan dan Ketahanan Pangan Rumah Tangga Tani di Empat Agroekosistem yang Berbeda - M. Eti Wulanjari; Sarjana Sarjana (Jurnal Ilmiah ESAI, 2010)
The authorizing of land is gradually narrowed because of rice field farming system is  inefficient and couldn’t be counted on as the main  farmer income. This paper is part of economic rural indicator of development analysis resume in four different agroecosystems, especially focused on the income structure and the food security of farmer household. This location is determined  through purposive system, because it represents the different agroecosystem area.The observation was held in several location represented different kinds of land, Banjarnegara district for dry lowland, Magelang district for dry upland, Grobogan for intensive rice field and Pati district for semi intensive rice field. This research was conduted using survey method, with 30 samples at Banjarnegara district, Magelang district and Pati district. Meanwhile, 29  samples were used at Grobogan district. The results of the research  show that (1) the segment of income farming system to  farmer income household is 67,65% in the dry upland (Magelang) and the lowest is 25,03% in the dry lowland (Banjarnegara); (2) The highest of food consumption is  47,5% in the intensive rice field (Grobogan) and the lowest is 24,93% in the dry upland (Magelang); (3) the ratio value  of food production compare to food need is more than 1, which indicated that farming system still  quarantee food security of farmer household. Key words:  income structure, food security, farmer household